PERILAKU PEMBELIAN TIDAK TERENCANA (IMPULSE BUYING) DI PUSAT PERBENJAAN MODERN DI SURABAYA (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
The aim of this research was to analyze the infuence of the fashion involvement and money available toward the impulse buying behaviors through positive emotion. The research was conducted in the biggest shopping center in Surabaya with the samples of 218 samples. The data analyses were by using SEM. The result of the research pointed out that fashion involvement signifcantly be infuenced toward the positive emotion and the impulse buying, the positive emotion was also infuenced signifcantly toward the impulse buying. Money available was infuenced signifcantly toward the positive emotion however was not signifcantly infuenced toward the impulse buying. Summary, purchasing activities were not caused by fashion-oriented impulse buying only, but also caused by planned impulse buying and reminder impulse buying.Key words: involvement, money, emotion, impulse buying